Cognitive functioning in bipolar disorder - Weathers, J (2012)
To align the neuropsychological functioning of our adult euthymic patient group with that reported in previous studies on euthymic bipolar disorder (BD), we used a neuropsychological battery that examined sustained attention (Rapid Visual Information Processing Task), verbal memory (California Verbal Learning Task), executive functioning (Intradimensional-Extradimensional Shift Task, Barrett Impulsivity Task, and Framing Task), and emotion responsiveness/regulation (Positive Affect/Negative Affect Scales, Behavioral Inhibition/Behavioral Activation Scale, and Affective Lability/Affective Intensity Scales) in patients versus healthy volunteers (HV). Our results corroborated existing evidence of reduced sustained attention, impaired verbal memory and executive functioning, and abnormal emotional responsiveness and regulation in euthymic BD relative to healthy controls (Chapter 2). To investigate how abnormal development of brain function in BD leads to deficits in decision-making, motor inhibition, and response flexibility, we examined child and adult BD using a novel risky decision-making task, and used cross-sectional (age x diagnosis) functional magnetic resonance (fMRI) designs to examine neural activation associated with motor inhibition and response flexibility in BD relative to HV. During the risky decision-making task, adult euthymic BD patients were no different from healthy controls in their proportion of risky lottery choices over a range of competing lotteries. This matched behavioral performance was associated with similar prefrontal and striatal brain activation between the patient and control groups during response, anticipation, and outcome phases of decision-making (Chapter 3). These results are different from previous studies that have shown increased risk taking during decision-making in euthymic BD. Similarly, young BD patients were no different from age-matched healthy and patient controls in their pattern of decision making during the risky choice task. This was evidenced by a similar number of risky lottery selections over the range of changing expected values between the young BD group and control groups (Chapter 4). Using a cross-sectional, fMRI analytic design during the stop signal task, we found that child and adult BD showed similar behavioral performance to child and adult HV during motor inhibition. However, this matched behavioral performance was associated with abnormal neural activation in patients relative to controls. Specifically, during unsuccessful motor inhibition, there was an age group x diagnosis interaction, with BD youth showing reduced activity in left and right ACC compared to both age-matched HV and adult BD, and adult BD showing increased activation in left ACC compared to healthy adults. During successful motor inhibition there was a main effect of diagnosis, with HV showing greater activity in left VPFC and right NAc compared to BD (Chapter 5). These neuroimaging data support existing laboratory-based evidence of motor inhibition impairments in BD relative to HV, and indicate brain dysregulation during motor control is important to BD pathophysiology. A previous behavioral study showed impaired response flexibility in young BD patients relative to age-matched controls when using the change task. Here, we used the change task during fMRI to examine response flexibility in child and adult BD compared to child and adult HV. We found that patient and control groups showed similar change signal reaction times in response to change cues. However, this matched behavioral performance was associated with abnormal age group x diagnosis activations in brain regions important in signal detection, response conflict, response inhibition, and sustained attention. Specifically, during successful change trials, child BD participants showed frontal, parietal, and temporal hyperactivation relative to healthy children and adult BD, while adult BD showed hypoactivation in these regions relative to healthy adults. These novel fMRI findings during the change task indicate impaired neural activation during response flexibility may be important to the pathophysiology of BD development.